A New Strategy for Selective Area Growth of Highly Uniform InGaAs/InP Multiple Quantum Well Nanowire Arrays for Optoelectronic Device Applications. (2nd July 2021) - Zhang, Fanlu; Zhang, Xutao; Li, Ziyuan; Yi, Ruixuan; Li, Zhe; Wang, Naiyin; Xu, Xiaoxue; Azimi, Zahra; Li, Li; Lysevych, Mykhaylo; Gan, Xuetao; Lu, Yuerui; et al.
Abstract: III‐V semiconductor nanowires with quantum wells (QWs) are promising for ultra‐compact light sources and photodetectors from visible to infrared spectral region. However, most of the reported InGaAs/InP QW nanowires are based on the wurtzite phase and exhibit non‐uniform morphology due to the complex heterostructure growth, making it challenging to incorporate multiple‐QWs (MQW) for optoelectronic applications. Here, a new strategy for the growth of InGaAs/InP MQW nanowire arrays by selective area metalorganic vapor phase epitaxy is reported. It is revealed that {110} faceted InP nanowires with mixed zincblende and wurtzite phases can be achieved, forming a critical base for the subsequent growth of highly‐uniform, taper‐free, hexagonal‐shaped MQW nanowire arrays with excellent optical properties. Room‐temperature lasing at the wavelength of ≈1 µm under optical pumping is achieved with a low threshold. By incorporating dopants to form an n + ‐i‐n + structure, InGaAs/InP 40‐QW nanowire array photodetectors are demonstrated with the broadband response (400–1600 nm) and high responsivities of 2175 A W −1 at 980 nm outperforming those of conventional planar InGaAs photodetectors. The results show that the new growth strategy is highly feasible to achieve high‐quality InGaAs/InP MQW nanowires for the development of future optoelectronic devices and integrated photonic systems. Abstract : A new facet engineering strategy is proposed to achieve the epitaxial growth of highly uniform InGaAs/InP multiple quantum well nanowires. The nanowires exhibit low threshold optically pumped lasing at room temperature and are fabricated into broadband photodetectors with high responsivity and fast response time. Such a growth strategy can pave the way for a wide range of nanoscale optoelectronic applications.